HIKMAH VIRUS CORONA DALAM PERSPEKTIF DAKWAH ISLAM - Muhammad Jamil Yusuf (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri (UIN) Ar-Raniry, 2020)
Corona virus has spread internationally as a new virus. The cure has not been found yet, and it caused the community to panic, anxious, and drained a lot of energy to prevent it. The number of positive cases continues to increase and it can't be predicted when it will end. Various regulations and appeals have been issued by the government so that people stay away from the crowd, keep their distance, just do activities at home, wear masks, wash their hands and always maintain cleanliness, including the prohibition of going back home during Idul Fitri 1441-H. The problem is, only some people obey while most others ignore it, which caused the government workload becoming heavier. Ideally, the community should take lessons from this situation by avoiding difficulties, strengthening efforts, being patient and surrender in order to find benefit in the corona virus pandemic. The community must be ready to face and respond to this pandemic positively, carefully, and not justify the way to meet the needs of life in this difficult time. Considering that corona virus information dissemination is very dominant through smart phone applications and digital technology, the Islamic da'wah movement must focus on increasing the digital literacy capabilities of the community to prevent anxiety, and excessive fear. The da'wah movement must be based on strengthening faith in God and strengthening the function of common sense by emphasizing the active role of millennial generation. Millennial generation is a generation that should be ready to carry out the mandate of change, tends to collaborate online and spend a lot of time with smartphones and digital technology. Therefore, this generation must get a touch of a more creative Islamic da'wah to affirm Islamic values by guiding them to collaborate to find wisdom and meaning stored behind the corona virus outbreak from various Islamic references and health sciences to be disseminated to the public.Keywords : Wisdom, Corona Virus, Islamic Da'wah